Structure of Revenues and Impact Thereof on the Rate of Indebtedness of Municipalities - Řezníčková, Kristýna (Public Governance, Administration and Finances Law Review, 2018)
In this article, the author examines in detail the structure of revenues of municipalities and the level of indebtedness thereof in particular periods. The author´s assumption is that the high rate of revenues obtained by the municipalities from the state, have a negative impact on indebtedness of the municipalities. The aim of the article is to prove that there is a relation between the indebtedness of municipalities and the kinds of revenues thereof. Therefore, the hypothesis the author will try to prove or disprove in her work, reads as follows: “The sources of municipal revenues are a very important aspect that may have a substantial effect on the economic results of every municipality.” The author in particular uses the method of analysis, synthesis and mostly in the second part of her work she also uses the comparative method.